IMMUNE RESPONSES IN ESOPHAGEAL CARCINOMA EC PATIENTS - S. Hashemi; B. Parhami; M.S. Enayat; K. Dowlatshahi; N.E. Day; N. Mohagheghpour (Tehran University of Medical Sciences, 1979)
General immune responses were studied in patients with esophageal carcinoma (EC) and were compared to those in normal individuals of similar age, sex and ethnic origin. There was a significant increase in the titer of "background" antibodies in the sera of cancer patients; however, this elevation was not associated with an increase in the levels of serum immunoglobulin. EC patients had a diminished number of E rosetting lymphocytes but normal proportion of EAC rosetting cells. Lymphocytes from a small but significant number of patients showed decreased responses to PHA when cultured in medium containing fetal calf serum. Plasma sample from these patients were capable of inhibiting the in vitro proliferate responses of lymphocytes to PPD.